A comparison of mosquito sampling methods in six Pacific Island countries - Adam T. Craig; Amanda K. Murphy; Charlie Ave; Nelson Ngaiorae; Lesieli Maha; Filisi Tonga; Charles Butafa; Vineshwaran Rama; Fata Paulo; Tabomoa Tinte; Tessa B. Knox; Holly Jian; et al. (One Health, 2025)
Outbreaks of arboviral diseases pose a significant threat to health security in Pacific Island countries and territories. In the absence of vaccines or treatments, effective vector control is critical to reduce risk and respond to outbreaks. This relies on sustainable mosquito surveillance strategies to identify vectors and guide control efforts. This study evaluated the performance and feasibility of three adult mosquito sampling methods—BG-Sentinel II (BGS) traps, BG Gravid Aedes Traps (GAT), and sweep netting (SWN)—in six Pacific countries: Cook Islands, Fiji, Kiribati, Samoa, Solomon Islands, and Tonga. Sampling followed a Latin square design across 54 sites in 18 locations. Data were analysed using a generalised linear mixed model and Simpson's Index for diversity. Qualitative interviews with public health staff captured operational experiences. 2815 mosquitoes were collected, with Aedes species comprising 61 %. Species composition varied significantly between countries (p < 0.05). BGS traps yielded considerably more mosquitoes than GAT and SWN (p < 0.05). No major species bias was observed across sampling methods. The public health staff interviewed emphasised the value of mentoring, co-design, and resourcing for operational research. Pacific context-specific challenges underscored the need for simple, durable tools for routine use, particularly if to be used in remote settings. This is the first multi-country study conducted in the Pacific to compare Aedes sampling methods.